2017
DOI: 10.1159/000455193
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Defense of Human Airway Epithelial Cells from Chronic Obstructive Pulmonary Disease Patients Induced by Acute Exposure to Nontypeable Haemophilus influenzae: Modulation by Cigarette Smoke

Abstract: Antimicrobial proteins and peptides (AMPs) are a central component of the antibacterial activity of airway epithelial cells. It has been proposed that a decrease in antibacterial lung defense contributes to an increased susceptibility to microbial infection in smokers and patients with chronic obstructive pulmonary disease (COPD). However, whether reduced AMP expression in the epithelium contributes to this lower defense is largely unknown. We investigated the bacterial killing activity and expression of AMPs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 59 publications
(80 reference statements)
4
53
0
Order By: Relevance
“…The advantage of this option is underlined by the observation that ALI-cultured airway epithelial cells derived from patients with mild or severe asthma retain characteristics of the distorted airway epithelium present in the patients lungs, and that the phenotypic differences relate to the severity of asthma (Gras et al, 2012). Similar observations have been reported in COPD (Amatngalim et al, 2017;Staudt et al, 2014), suggesting that the lung microenvironment in these inflammatory lung diseases causes (epigenetic) changes in epithelial cells resulting in partial persistence of the phenotype in culture.…”
Section: Primary Lung Epithelial Cellsmentioning
confidence: 63%
See 2 more Smart Citations
“…The advantage of this option is underlined by the observation that ALI-cultured airway epithelial cells derived from patients with mild or severe asthma retain characteristics of the distorted airway epithelium present in the patients lungs, and that the phenotypic differences relate to the severity of asthma (Gras et al, 2012). Similar observations have been reported in COPD (Amatngalim et al, 2017;Staudt et al, 2014), suggesting that the lung microenvironment in these inflammatory lung diseases causes (epigenetic) changes in epithelial cells resulting in partial persistence of the phenotype in culture.…”
Section: Primary Lung Epithelial Cellsmentioning
confidence: 63%
“…We recently showed that the ALI-differentiated cultures used in our laboratory for exposures to e.g. diesel exhaust (Zarcone et al, 2016;Zarcone et al, 2017) or cigarette smoke (Amatngalim et al, 2015;Amatngalim et al, 2017) show higher expression of various genes involved in biotransformation compared to undifferentiated cultures (Boei et al, 2016). Furthermore, we showed that undifferentiated cultures, in contrast to differentiated cultures, are incapable of metabolic conversion of a variety of different p450 substrates.…”
Section: Primary Lung Epithelial Cellsmentioning
confidence: 85%
See 1 more Smart Citation
“…Our data demonstrating striking similarities in the epithelial immune profile in response to cannabis and tobacco, suggests that the former will impact host defences. Tobacco has been demonstrated to impact host defence peptide induction in airway epithelial cells by nontypeable Haemophilus influenzae with a concomitant increase in IL‐8 expression (Amatngalim et al, ). Our experimental dataset in this study did not include a pathogen challenge, precluding our ability confirm the tobacco smoke induced suppression of host defence peptides or to extend the results to cannabis smoke.…”
Section: Discussionmentioning
confidence: 99%
“…However, long-standing and dysregulated inflammation in the airways is a key feature of several states of disease, e.g., in COPD and cystic fibrosis [11][12][13]. Furthermore, without a preceding chronic airway inflammation, the host response may cause tissue damage [10,14].…”
mentioning
confidence: 99%